Nonlinear hydrodynamic Langmuir waves in fully degenerate relativistic plasma. (April 2015) - Haas, F; Kourakis, I
Abstract The combined effect of special relativity and electron degeneracy on Langmuir waves is analyzed by utilizing a rigorous fully relativistic hydrodynamic model. Assuming a traveling wave solution form, a set of conservation laws is identified, together with a pseudo-potential function depending on the relativistic parameter pF/(mc) (where pF is the Fermi momentum, m is the mass of the charge carriers and c the speed of light), as well as on the amplitude of the electrostatic energy perturbation.